Dominasi Teknologi dan Kapitalisme (Perspektif Teori Kritis Herbert Marcuse) - Kornelius Ayub Dwi Winarso (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2022)
The age continues to move forward. Such progress is marked by the latest developments in the world of science and technology. In the context of community life, technological progress embraces capitalism so as to form an order characterized by dominance in various aspect. This paper focuses on the discussion around the dominance of technology and capitalism in an effort to understand the real phenomena that are being faced by all levels of society. The theory used to highlight this problem is the critical theory of Herbert Marcuse. The purpose of this study process is to bring up new discourse in shaping a more proportional society in the context to face up the Industrial Revolution Era 4.0 and Covid-19 Pandemic impact in Indonesia by new educational perspective